Pengembangan dan Kebijakan Sektor Informal Malam di Kalimantan Selatan - Witanti, Sri; Misransyah (Jurnal Aplikasi Manajemen, 2013)
This research aims to 1) Explain how the difference correlation between scale of business activities with development of the amount of credit has been given to Informal evening Sector. 2) Explain how the correlation of capital factor, experience, education, labor, hours of work , revolving working capital that affect on the acceptance of rupiah per month in Informal evening Sector at South Kalimantan. 3) Explain how the correlation of knowledge factors, talent and expertise that affect on the entrepreneurship on informal evening sector at South Kalimantan. This research is a descriptive research type (Descriptive Research) and the explanations research type (Explanatory Research) that conducted by Analysis Secondary Data and Primary Data. Primary data collection was conducted by the Research Methods which were analyzed using descriptive statistical analysis (tablature) and Differential (Differences Testing and double Regression) With Social Research Statistics Program Version 17.0 . (Santoso , 2009). Areas of this research carried out in South Kalimantan as many as 14 fair consists of: Banjarmasin 7 Fair, Banjarbaru 3 fair andMartapura 4 fair, with a population of 627 people in the informal evening sector at Banjarmasin, while the fair at Banjarbaru and Martapura as much as 423 people in the informal sector. Sample required as much as 150 respondents that randomly selected (purposive random sampling) and is considered representative to represent the population to be studied. This research analyzed with qualitative and quantitative is a form Description and Explanatory research on the informal evening sector in South Kalimantan. The results of this research showed, 1) Dominated by male workers who are married, have dependents, aged 20-30 years, with a high school education or equivalent and they are majority from South Kalimantan, 2) To develop and the informal evening sector policy that effective administration of the loans granted by financial institutions is the credit amount > Rp5.000.000, - thereby increasing public acceptance of the informal evening sector, the greater the amount of loans to the entrepreneur informal evening sector, then the greater acceptance will be received by the public who engaged in the informal evening sector in South Kalimantan, 3) factors working capital and labor are influence. Not Influential Factors of experience, education, labor, hours of work and the business turnover of the informal evening sector enterprises reception at South Kalimantan, 4) factors working knowledge, talent and expertise affect the entrepreneurship in informal evening sector at South Kalimantan.